Changes in Bacterial Community Structure and Enriched Functional Bacteria Associated With Turfgrass Monoculture - Jeon, Chang-Wook; Kim, Da-Ran; Bae, Eun-Ji; Kwak, Youn-Sig (Frontiers in Bioengineering and Biotechnology, 2021)
Microbial communities are involved in many aspects of plant health. There is increasing attention being paid to utilizing microbial communities to improve plant health while reducing management inputs. Thus, the objectives of this research were to assess changes in the rhizosphere bacterial community structures associated with long-term turfgrass monoculture and to demonstrate the feasibility of using keystone bacteria as beneficial biocontrol agents. Rhizosphere samples were collected from 2-, 13- and 25-year turfgrass monocultures. Large patch disease, caused by the fungal pathogen Rhizoctonia solani, is a significant threat to turfgrass cultivation. The 13-year monoculture field had a higher pathogen population density than both the 2- and 25-year monoculture fields. Analyses of the rhizosphere bacterial communities revealed that Streptomyces was dominant in the 2-year field and Burkholderia was enriched in the 25-year field. Based on the culturable bacteria in the rhizospheres, Streptomyces neyagawaensis J6 and Burkholderia vietnamiensis J10 were obtained from the 2- and 25-year fields, respectively. Application of S. neyagawaensis J6 and B. vietnamiensis J10 led to excellent inhibition of large patch disease as well as enhanced tolerance against drought and temperature stresses. The results showed that the selected keystone taxa could be developed as biocontrol and abiotic stress-tolerant agents for turfgrass cultivation.